Taekwondo Training Center Dengan Pendekatan Arsitektur Metafora Tangible Di Pekanbaru - Rahman, Fadli; Aldy, Pedia; Susilawati, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The development and achievement of Taekwondo from Riau province on the National level in 2013 began to move forward rapidly and also the rise of Riau's position to the 4th rankin the National level had made Taekwondo of Riau province began to be noticed by the Taekwondo Big Executive Board of Indonesia (PBTI). It is necessary to support various facilities that can accommodate all activities of Taekwondo to get better performance. Due to the lack of coordinating institution that facilitate Taekwondo activities starting from thelodging, the field and most important thing is the place to do the exercises. The approach of the design will use Tangible Metaphor Architecture which will apply Taekwondo shape andcharacter, so that people can recognize the function of the building just by looking at the physical appearance of the building and produce a more modern formation. The purpose is toproduce a more expressive architecture by trying to move information from a subject to a building. The results is Taekwondo Training Center will implement the formation of Splitmovement to the form of building because Split is a typical movement of Taekwondo is very well known by people.Keywords: Taekwondo, Tangible Metaphor, Riau